Linguistic Variation in the Minimalist Framework. Ed. by Carme Picallo - Mireia Marimon (Universitat Autònoma de Barcelona, 2014)
This is a review of the book Linguistic Variation in the Minimalist Framework, edited by M. Carme Picallo (UAB). 2014. Oxford: Oxford University Press.